The self-driven child : the science and sense of giving your kids more control over their lives - Stixrud, William R.; Johnson, Ned, 1970- (New York, New York : Viking, an imprint of Penguin Random House LLC, 2018)
A clinical psychologist and a test-prep expert combine cutting-edge brain science with insights from their work with families to outline a case for giving children more freedom to unleash their full potential.
Includes bibliographical references (pages 327-351) and index.
PB
Keywords: Achievement motivation in children; Stress management for children; Self-reliance in children; Parenting; Child rearing; EDUCATION / Parent Participation; EDUCATION / Educational Psychology; FAMILY & RELATIONSHIPS / Parenting / General; EDUCATION / Educational Psychology; EDUCATION / Parent Participation; FAMILY & RELATIONSHIPS / Parenting / General